About makom melodies adapted for orchestra of uzbek folk instruments - Abdujalil Abdusattorov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
In this article, given the information about the classification of musical works created in the style of makom by famous composers of Uzbekistan for orchestra of folk instruments. There will also be given a brief commentary on musical works created in the tradition of makom.